Determination of HIV Status in Sexually Transmitted Diseases in Shanti Id Clinic Vadodara, Gujarat, India - Chopra, Narendra Kumar (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
The prospective study was carried out at Shanti infectious diseases clinic at Vadodara, Gujarat, India from January 2013 to May 2020 with following objectives: Objectives: 1. For detecting prevalence of HIV infection in sexually transmitted diseases attending at Shanti ID Clinic. Vadodara is an industrial city of India in south Gujarat at border of Madhya Pradesh (M.P) and Maharashtra approximately 300 miles from Mumbai. 2.To study in detail incidence of sexually transmitted infections (S.T.I) in Vadodara City of South Gujarat in India. S.T.I can increase both HIV negative person’s risk of becoming infected with HIV positive person’s risk of transmitting HIV to someone else. 3.The study explores how STI may increase of sexual HIV transmission; how STI may undermine our HIV prevention strategies? And What we can do about it? 4.There is strong association between bacterial and viral sexually transmitted infections and both the acquisition and transmission of HIV infection Males accounted for 317 (79.23%) of the 400 instances of sexually transmitted diseases, while females accounted for 83 (20.75%). The Elisa test was used to screen for HIV and was confirmed by a Western blot test. 300 instances (75.00%) were between the ages of 20 and 50, 34 cases (8.55%) were between the ages of 0 and 20, and 66 cases (916.25%) were over the age of 50. Out of 400 patients, 87 cases (21.75%) had syphilis, 45 cases (11.25%) had cancroid, 73 cases (18.25%) had gonorrhoea, 110 cases (27.50%) had genital herpes, and 11 cases (2.75%) had moll-scum contagiosum.There were 44 cases of genital scabies (11%), 9 cases of CMV infection (2.755%), and 21 cases of lympho-granuloma venerium (5.24%). 67 cases (16.76%) of 400 cases of sexually transmitted diseases tested positive for HIV, with 61 cases (91.04%) being HIV1 and the remaining 6 cases (8.96%) being HIV2.Despite the fact that there is a probable association between STIs and HIV risk, intervention research have been unsatisfactory. This does not rule out a causal relationship, but more research into the mechanisms of action, as well as the design and implementation of interventions, is needed.